The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5935/abc.20160134
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Serum Resistin and Leptin Levels Linked to Coronary Artery Disease

Abstract: BackgroundClinical studies have demonstrated that adipocytokines play an important role in developing atherosclerotic cardiovascular diseases.ObjectiveThe aim of study was to evaluate the relationship between serum resistin and leptin levels with obesity and coronary artery disease (CAD).MethodsIn a cross-sectional study, we assessed the levels of serum resistin and leptin, C-reactive protein (CRP), lipid profile and cardiac enzyme tests (AST, CPK, LDH, CK-MB) in 40 CAD patients compared to 40 healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 37 publications
(78 reference statements)
3
28
1
1
Order By: Relevance
“…Consistent with our studies, several studies have reported serum leptin levels to be significantly elevated in CAD patients [4, 25-27], suggesting the role of leptin as a mediator in human atherosclerotic. A large prospective study was conducted to examine that the raised leptin levels may identify men at increased risk of a coronary event in the West of Scotland Coronary Prevention Study [26].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with our studies, several studies have reported serum leptin levels to be significantly elevated in CAD patients [4, 25-27], suggesting the role of leptin as a mediator in human atherosclerotic. A large prospective study was conducted to examine that the raised leptin levels may identify men at increased risk of a coronary event in the West of Scotland Coronary Prevention Study [26].…”
Section: Discussionsupporting
confidence: 81%
“…Leptin is a cytokine, which is released from the adipose tissue and it acts on the hypothalamus to promote weight loss, both by reducing appetite and food intake and by increasing energy expenditure [3, 4]. Leptin contributes to the inflammatory processes related to obesity in both vascular and non-vascular tissues [5, 6], and activates endothelial cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Montazerifar et al indicated that Leptin levels were significantly higher in abdominal obese patients than those in patients without abdominal obesity or in the control group. This result was partly consistent with earlier reports …”
Section: Discussionmentioning
confidence: 98%
“…High serum leptin levels have been observed in patients with CHD (33). There is a strong correlation between both circulating and adipose tissue levels of leptin and serum c-reactive protein (CRP) in obese women (34).…”
Section: Potential Mechanismsmentioning
confidence: 99%